Dihydromyricetin inhibits NLRP3 inflammasome‐dependent pyroptosis by activating the Nrf2 signaling pathway in vascular endothelial cells. (29th November 2017) - Hu, Qin; Zhang, Ting; Yi, Long; Zhou, Xi; Mi, Mantian
Abstract: Increasing evidence demonstrates that pyroptosis, pro‐inflammatory programmed cell death, is linked to atherosclerosis; however, the underlying mechanisms remain to be elucidated. Dihydromyricetin (DHM), a natural flavonoid, was reported to exert anti‐oxidative and anti‐inflammatory bioactivities. However, the effect of DHM on atherosclerosis‐related pyroptosis has not been studied. In the present study, palmitic acid (PA) treatment led to pyroptosis in human umbilical vein endothelial cells (HUVECs), as evidenced by caspase‐1 activation, LDH release, and propidium iodide‐positive staining; enhanced the maturation and release of proinflammatory cytokine IL‐1β and activation of the NLRP3 inflammasome; and markedly increased intracellular reactive oxygen species (ROS) and mitochondrial ROS (mtROS) levels. Moreover, NLRP3 siRNA transfection or treatment with inhibitors efficiently suppressed PA‐induced pyroptosis, and pretreatment with total ROS scavenger or mtROS scavenger attenuated PA‐induced NLRP3 inflammasome activation and subsequent pyroptosis. However, DHM pretreatment inhibited PA‐induced pyroptotic cell death by increasing cell viability, decreasing LDH and IL‐1β release, improving cell membrane integrity, and abolishing caspase‐1 cleavage and subsequent IL‐1β maturation. We also found that DHM pre‐treatment remarkably reduced the levels of intracellular ROS and mtROS and activated the Nrf2 signaling pathway. Moreover, knockdown of Nrf2 by siRNA abrogated the inhibitory effects of DHM on ROS generation and subsequent PA‐induced pyroptosis. Together, these results indicate that the Nrf2 signaling pathway plays a role, as least in part, in the DHM‐mediated improvement in PA‐induced pyroptosis in vascular endothelial cells, which implies the underlying medicinal value of DHM targeting immune/inflammatory‐related diseases, such as atherosclerosis. © 2017 BioFactors, 44(2):123–136, 2018